Order and disorder in the international system - Krishna-Hensel, Sai Felicia (Global interdisciplinary studies series, 2010)
An examination of the complex international system of the twenty-first century from a variety of perspectives. Proceeding from critical theoretical perspectives and incorporating case studies, the chapters focus on broad trends as well as micro-realities of a Post-Westphalian international system.